Dietary Reference Values for riboflavin. (7th August 2017) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Nowicka, Grażyna; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) derives dietary reference values (DRVs) for riboflavin. The Panel considers that the inflection point in the urinary riboflavin excretion curve in relation to riboflavin intake reflects body saturation and can be used as a biomarker of adequate riboflavin status. The Panel also considers that erythrocyte glutathione reductase activation coefficient is a useful biomarker, but has limitations. For adults, the Panel considers that average requirements (ARs) and population reference intakes (PRIs) can be determined from the weighted mean of riboflavin intake associated with the inflection point in the urinary riboflavin excretion curve reported in four intervention studies. PRIs are derived for adults and children assuming a coefficient of variation of 10%, in the absence of information on the variability in the requirement and to account for the potential effect of physical activity and the methylenetetrahydrofolate reductase 677TT genotype. For adults, the AR and PRI are set at 1.3 and 1.6 mg/day. For infants aged 7–11 months, an adequate intake of 0.4 mg/day is set by upward extrapolation from the riboflavin intake of exclusively breastfed infants aged 0–6 months. For children, ARs are derived by downward extrapolation from the adult AR, applying allometric scaling and growth factors and considering differences in reference body weight. For children of both sexes aged 1–17 years, ARs range between 0.5 and 1.4 mg/day, and PRIs between 0.6 and 1.6 mg/day. For pregnant or lactating women, additional requirements are considered, to account for fetal uptake and riboflavin accretion in the placenta during pregnancy or the losses through breast milk, and PRIs of 1.9 and 2.0 mg/day, respectively, are derived. Abstract : This publication is linked to the following EFSA Supporting Publications article:http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1268/full